PENGEMBANGAN PEMBELAJARAN MAHAROT AL-ISTIMA BERBASIS MULTIMEDIA DI IAI CIPASUNG TASIKMALAYA - Asep Maulana (Edulead : Journal of Education Management, 2021)
This research aims to (1) develop internet-based instructional multimedia on Arabic listening course in IAIC Tasikmalaya, (2) describe the feasibility of internet-based intructional multimedia on Arabic listening course in IAIC Tasikmalaya, and (3) describe the use of of internet-based instructional multimedia on Arabic listening course in IAIC Tasikmalaya. This research method using the R & D (research and development) refers to research model created by Borg & Gall. The results showed that (1) development of internet-based intructional multimedia on Arabic listening course presented in the form of power point complicated by video and intructional materials, (2) the product is well worth about 3.60 level of intructional material feasibility and 3.70 level of multimedia feasibility and it can be received by students with average 3.30 level of their assessment, (3) the product is used with the classical and independent instructional model.